Marie-Helene Bourcier: Queer Zones 3. Identites, cultures et politiques.(Book review) - Baril, Alexandre (Recherches Feministes, 2012)
Compte-rendu du livre Queer Zones 3. Identites, cultures et politiques de Sam Bourcier.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; arts; cours; discipline; europe; france; identités LGBTQIA2+; lit4700; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sexualité; sociologie; thématiques; études culturelles; études littéraires

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Quelle place pour les femmes trans au sein des mouvements féministes ? / Excluded. Making Feminist and Queer Movements More Inclusive, de Julia Serano, Seal Press, 338 p. - Baril, Alexandre (Spirale : arts • lettres • sciences humaines, 2014)
Un article de la revue Spirale, diffusée par la plateforme Érudit.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme inclusif; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; terf; thématiques; transféminisme; transphobie; études trans*